Increase in the Size of an Intracardiac Thrombus during Dabigatran Therapy (110 mg b.i.d.) in an Acute Cardioembolic Stroke Patient - Emi Tabata; Masahiro Yasaka; Yoshiyuki Wakugawa; Motohiro Komori; Kohta Mori; Yuichiro Tsurusaki; Kazuhito Kokuba; Yoshiki Sambongi; Koichiro Maeda; Yasushi Okada (Cerebrovascular Diseases Extra, 2013)
We report a case of atrial fibrillation in a patient in whom a mobile thrombus in the left atrial appendage increased in size after low-dose dabigatran therapy. A 74-year-old man was admitted to our hospital because of sudden onset of right hemiplasia and dysarthria. On admission, his National Institutes of Health Stroke Scale score was three. Axial diffusion-weighted magnetic resonance images and magnetic resonance angiography images showed hyperintense signals in the left front-parietal cerebral cortex without any intracranial stenotic lesions, and acute cardioembolic stroke associated with nonvalvular atrial fibrillation was diagnosed. Transesophageal echocardiography revealed a mobile thrombosis (1.0 × 2.2 cm) in the left atrial appendage, and dabigatran therapy (110 mg b.i.d.) was initiated to prevent stroke recurrence. Transesophageal echocardiography performed 6 days later revealed that the size of the thrombus had increased to 1.5 × 3.0 cm. Medication was changed to warfarin, and the thrombosis subsequently decreased in size. The patient did not have a recurrent stroke and was discharged with a National Institutes of Health Stroke Scale score of zero. This case demonstrates that low-dose dabigatran may not be effective in reducing the size of a thrombus.